Novel MRPS9-ALK Fusion Mutation in a Lung Adenocarcinoma Patient: A Case Report - Zhou, Huamiao; Xu, Binyue; Xu, Jili; Zhu, Guomeng; Guo, Yong (Frontiers in Oncology, 2021)
Anaplastic lymphoma kinase (ALK) rearrangements account for approximately 5–6% of non–small-cell lung cancer (NSCLC) patients. In this study, a case of lung adenocarcinoma harboring a novel MRPS9-ALK fusion is reported. The patient responded well to the first and second generation of ALK-tyrosine kinase inhibitors (ALK-TKIs) (crizotinib then alectinib), as her imaging findings and clinical symptoms significantly improved. At last follow-up, over 21 months of overall survival (OS) has been achieved since ALK-TKI treatment. The progression-free survival (PFS) is already ten months since alectinib. The adverse effects were manageable. The case presented here provides first clinical evidence of the efficacy of ALK-TKIs in NSCLC patients with MRPS9-ALK fusion.